2011
DOI: 10.1111/j.2044-8287.2010.02008.x
|View full text |Cite
|
Sign up to set email alerts
|

The experience of diabetic retinopathy: A qualitative study

Abstract: The findings highlight the importance of providing these individuals with appropriate professional support to facilitate the management of both conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…Studies exploring psychological adjustment in individuals with diabetes and visual impairment (20) showed that even people with mild DR express feelings of uncertainty and vulnerability at the prospect of vision loss. Similarly to other industrialized countries, the social security system in Italy provides free access to eye care services, such as screening, assessment and treatment for diabetic 8 retinopathy, although in many instances visits are carried out on a fee-for-service basis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies exploring psychological adjustment in individuals with diabetes and visual impairment (20) showed that even people with mild DR express feelings of uncertainty and vulnerability at the prospect of vision loss. Similarly to other industrialized countries, the social security system in Italy provides free access to eye care services, such as screening, assessment and treatment for diabetic 8 retinopathy, although in many instances visits are carried out on a fee-for-service basis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, focus group participants have described increased social isolation as a result of no longer being able to drive due to DR 26,31 . Recently Devenney et al 27 . found that practical difficulties associated with patients participating in social activities led them to withdraw from social situations and consequently become more socially isolated.…”
Section: Impact Of Dr On Social Well‐beingmentioning
confidence: 99%
“…Similarly, patients undergoing group therapy for DR reported that negative public reactions to vision loss and perceived social stigma fostered feelings of isolation 30 . Patients have also described anxiety over maintaining friendships or acquaintances, or meeting new people because of difficulty recognizing faces, 31 or because of becoming more dependent and feeling burdensome 27 . Younger participants with DR described visual impairment as a major deterrent to finding potential partners and forming romantic relationships 30 .…”
Section: Impact Of Dr On Social Well‐beingmentioning
confidence: 99%
“…These studies found that patients with a diabetes complication or comorbid condition frequently experienced a sense of dependence, social isolation, and the loss of social and occupational roles [56,65]. Further, patients expressed difficulty interpreting severe symptoms of their condition and knowing when to seek medical attention [57], understanding risks of developing complications associated with diabetes [58,61], maintaining self-care regimens [57,60], communicating with health professionals [59,64], and taking prescribed medications for other health conditions [62].…”
Section: Complications and Comorbiditiesmentioning
confidence: 95%
“…Several qualitative studies have explored diabetes patients' experiences of living with and treating of a single diabetes complication or comorbid condition, including diabetic retinopathy, myocardial infarction, diabetic foot infections, and depression [56][57][58][59][60][61][62][63][64][65]. These studies found that patients with a diabetes complication or comorbid condition frequently experienced a sense of dependence, social isolation, and the loss of social and occupational roles [56,65].…”
Section: Complications and Comorbiditiesmentioning
confidence: 97%